(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2018)
Different concentration extracts of Cassia occidentalis (Caesalpiniaceae) leaves were screened for their antimicrobial activity against Salmonella Typhimurium. The pattern of inhibition was varied with the concentration used. Antibacterial activity of the extracts at different concentrations on the S. Typhimurium was recorded with no activity at 20 mg/mL. Nevertheless, at concentrations of 40, 60, 80 and 100 mg/mL, activity was observed. This activity was seen increased as the concentration increases. At the minimum bactericidal concentration (MBC) of 60 mg/mL, the bacteria were killed with no tidal activity at 30 mg/mL. The antibacterial activity of Cassia occidentalis leaf extract was recorded at concentrations of 40 mg/mL (12 mm), 60 mg/mL (15 mm), 80 mg/mL (16 mm) and 100 mg/mL (18 mm) with a minimum inhibitory concentration (MIC) of 30 mg/mL and MBC of 60 mg/mL. This was due to the presence of phytochemical compounds. Some of these compounds were found in a trace amount, whereas saponin was present high amount, flavonoids were present in a moderate amount, while tannins, glycoside, cardiac glycosides, steroids, saponin glycoside, anthraquinones and volatile oil were present in trace amount. However, balsam and alkaloid are not detected.